Epidemiological profile of secondary headaches in a hospital in Salvador-BA: Proposal for a research project (Research, Society and Development, 2022)
Secondary headaches are aggravations to the normal functioning of an individual's nervous system, resulting from a primary cause, which may include bacterial and viral infections, fibromyalgias, aneurysms, brain tumors, among others. Usually, the causal factors of secondary headaches deserve immediate management, on the part of the responsible health professional, as they can encompass more serious etiologies, which often go beyond the therapeutic measures offered by Primary Care, and require a broader coverage, present in hospitals. . Therefore, the objective of this study was to establish a structuring proposal for conducting an analysis of the epidemiological profile of secondary headaches in the emergency department of a referral hospital in Neurology, in the city of Salvador, Bahia. For this, the authors built a research project model, aiming to instruct the scientific community about the steps to be followed to carry out the study, so that it can be replicated in the future. Among the results presented, there is the proposal of an analytical method to define an epidemiological profile of secondary headaches in the emergency room of that hospital, in Salvador, Bahia. Finally, it is concluded that secondary headaches are fundamental clinical manifestations for the establishment of an etiological disease, especially within the field of emergency. Therefore, this study is of significant importance, since it has the function of establishing a whole method to be replicated by the scientific community regarding the analysis of the epidemiological profile of such a disease in the mentioned place.